Development of Stem-Based Modules on The Growth and Development of Living Things for Students Fases (SMA/MA) - Regiani Zahira; Renny Risdawati; Aulia Afza (Pascasarjana, Mataram University, 2026)
The availability of appropriate and structured teaching materials is a crucial aspect in supporting the effectiveness of the learning process. At SMA Negeri 2 Lubuk Sikaping, teachers use the Ministry of Education and Culture's guidebook as the primary reference during the teaching and learning process. However, to strengthen the learning process and adapt to students' needs, teachers also develop independent teaching materials in the form of modules, but these modules still contain the 2013 curriculum. One relevant approach to developing teaching materials is Science, Technology, Engineering, and Mathematics (STEM), particularly in the growth and development of living things. This requires students to implement projects, requiring them to utilize their skills in designing, observing, and reporting on their projects. This research is a research and development (R&D) study using the 4D model (Define, Design, Develop, and Disseminate), but is limited to the Development stage. The instruments used in this study include a validity questionnaire and a practicality questionnaire. The validity test was conducted by two lecturers and one teacher, while the practicality test involved one biology teacher and 30 students from Phase F (11) class. Validation results by lecturers and teachers indicate that the developed module has a very high validity rate, with a percentage of 94.68%. The module's practicality was also deemed highly practical by both teachers (94%) and students (91.74%). Thus, this STEM-based printed module is deemed highly valid and practical as a teaching material for the growth and development of living things at the high school level